0810 Management of Narcolepsy In A Patient With Severe Chronic Iron Deficiency: The Importance of Addressing Nutritional Deficiencies In The Treatment of Narcolepsy and Hypersomnias. (25th May 2022) - Baldridge, Scott; Khan, Yousaf; Ghildiyal, Naomi; Monceaux, Brittany; Asghar, Sheila; Liendo, Cesar; Chernyshev, Oleg
Abstract: Introduction: Since iron is a cofactor used in the synthesis of CNS dopamine, some of which is then converted into norepinephrine, CNS iron deficiency will have an impact on the availability of dopamine and norepinephrine. Medications for narcolepsy and hypersomnia, such as stimulants and wakefulness medications, are dependent on the availability of these neurotransmitters to achieve their clinical response. Unrecognized and untreated nutritional deficiencies may contribute to inadequate responses to treatment of these sleep disorders. Report of Cases: A 26-year-old female with a history of iron deficiency since her pre-kindergarten health evaluation had a history of inadequate responses to stimulants and wakefulness medications. Additional labs were drawn to evaluate for nutritional deficiencies that could be contributing to the combination of fatigue and hypersomnolence. These revealed continued severe iron deficiency along with vitamin B6, B12, and D deficiencies. The treatment plan then expanded to include treatment of the nutritional deficiencies and a trial of pitolisant, which works to increase histamine levels in the brain. Sadly, pitolisant resulted in intolerable headaches, so it was discontinued. Conclusion: This author feels that patients with hypersomnia warrant a broader approach that includes evaluating for nutritional deficiencies which may contribute to fatigue and hypersomnolence. In this case, the plan was to address the patient's nutritional deficiencies and switch to pitolisant which mediates increased CNS histamine levels. This was unsuccessful due to the side effect of increased frequency and intensity of headaches related to pitolisant. Treating her iron deficiency with iron infusions should increase CNS synthesis of dopamine and norepinephrine. She may now have a better response to stimulants or wakefulness medications which depend on the availability of these neurotransmitters. She may also benefit from combination therapy by adding sodium oxybate to one of these medications. Support (If Any):